Internal and external factors influencing the transformation of the traditional marriage ceremony - Iliyaskyzy Д.; Ш.Т. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
During the era of the Joseon Dynasty the wedding ceremony held special significance and was accompanied by numerous traditions and rituals. Although most of them have been forgotten, some are still preserved to this day. The purpose of this article is to explore Korean traditional weddings starting from the Joseon Dynasty (1392-1910), analyze the influence of internal and external factors on the transformation of wedding traditions, conduct a historical analysis of the order of a traditional wedding ceremony, study changes in Korean wedding ceremonies and their preservation in a globalized world, as well as research the procedure of a modern wedding ceremony. The author highlights traditional wedding ceremonies that almost disappeared in the 1960s but were revived in 1982 under the name «traditional wedding». Historical and anthropological analysis, general theoretical methods (analysis, synthesis, abstraction), document and source analysis were applied in this work. The author also conducted a documentary analysis of laws that influence the transformation and simplification of traditional weddings. As a result of the conducted research, the author carried out a comparative analysis of traditional and modern weddings in South Korea and concluded that globalization has a significant influence on the transformation of wedding ceremonies. It was also noted that wedding rituals in Korea are regulated by the government. Hypothesis: Koreans have preserved the traditional wedding, but have changed some of its elements, partly influenced by modern Western elements, and have successfully synthesized it with Western elements. The traditional wedding ceremony has been «reorganized» in accordance with the requirements of modern society. The traditional wedding ceremony has been « reorganized» to meet the requirements of modern society.